Programmable Molecular Scissors: Applications of a New Tool for Genome Editing in Biotech - Subbroto Kumar Saha; Forhad Karim Saikot; Md. Shahedur Rahman; Mohammad Abu Hena Mostofa Jamal; S.M. Khaledur Rahman; S.M. Riazul Islam; Ki-Hyun Kim (Elsevier, 2019)
Targeted genome editing is an advanced technique that enables precise modification of the nucleic acid sequences in a genome. Genome editing is typically performed using tools, such as molecular scissors, to cut a defined location in a specific gene. Genome editing has impacted various fields of biotechnology, such as agriculture; biopharmaceutical production; studies on the structure, regulation, and function of the genome; and the creation of transgenic organisms and cell lines. Although genome editing is used frequently, it has several limitations. Here, we provide an overview of well-studied genome-editing nucleases, including single-stranded oligodeoxynucleotides (ssODNs), transcription activator-like effector nucleases (TALENs), zinc-finger nucleases (ZFNs), and CRISPR-Cas9 RNA-guided nucleases (CRISPR-Cas9). To this end, we describe the progress toward editable nuclease-based therapies and discuss the minimization of off-target mutagenesis. Future prospects of this challenging scientific field are also discussed. Keywords: genome editing, nucleases, DSB, NHEJ, HDR, ZFNs, TALENs, CRISPR-Cas9, ssODNs, off-target mutagenesis